A simple method for the isolation and purification of resveratrol from Polygonum cuspidatum - Dong-Geng Wang; Wen-Ying Liu; Guang-Tong Chen (Elsevier, 2013)
Resveratrol, a polyphenol compound with strong biological activity, has been widely used in medicine, health products and cosmetic industries. It is also the main active component of Polygonum cuspidatum, a well-known traditional Chinese medicine. We developed a simple and effective method for the preparation of resveratrol from P. cuspidatum. The whole preparative process consisted of reflux extraction, filtering, hydrolyzing, liquidâliquid extraction and eluting. Filtering is to remove non polar or less polar compounds and debris fragments from the extract. Hydrolyzing is to transform polydatin to resveratrol to improve the yield of resveratrol. Eluting is to remove impurities including strong acidic and water-soluble compounds. By acid hydrolysis of glycoside (polydatin), the yield of resveratrol increased about 4-fold. The extraction recovery in different stages was high, and the content of resveratrol in the final product was over 73.8%. Compared with other methods reported, this technology is eco-friendly, easier to perform, and also has a lower cost. Keywords: Polygonum cuspidatum, Resveratrol, Solvent extraction, Purification